The Relationship Between Myopia and Hypertension in Open-Angle Glaucoma Patients at Methodist Hospital in 2023 - Billy Cristover Tarigan; Lylys Surjani; Inda Meirani Sinaga; Mawar Gloria Tarigan; Dwi Lunarta Siahaan (Universitas Methodist Indonesia, 2024)
Background: Glaucoma is the second leading cause of global blindnessafter cataract. Glaucoma is thought to occur due to increased intraocularpressure (IOP) causing changes in the optic nerve and field of vision.Objective: To find out whether there is a relationship betweenhypertension and myopia in open angle glaucoma patients at MethodistHospital in 2023.Method: This research was conducted in an analytical observationalmanner with an approach using a cross sectional design, namely only for amoment or looking at the relationship between Myopia and Hypertensionin Open Angle Glaucoma Patients at Methodist Hospital in 2023 at thetime the research took place with medical record data of 74 samples basedon inclusion and exclusion criteria. .Results: From the results of this study, it was found that there was arelationship between myopia and open angle glaucoma with p – value =0.000 (<0.05). There is a relationship between hypertension and openangle glaucoma with p – value = 0.016 (<0.05).Conclusion: There is a relationship between hypertension and myopia inopen angle glaucoma patients